Kajian Roma 12:2 Berkaitan dengan Konsep Pengudusan Pada Wanita Kristen dan Implikasinya - Sharon Evangelica Manete (LPPM STT Baptis Kalvari, 2021)
The understanding of sanctification has so far discussed humans in general without distinguishing the dynamics of gender in it. A micro approach is needed so that women as objects of salvation can see God's inclusion after they receive salvation. In a culture that was thickly patriarchal in the past, it took courage to see aspects of sanctification from the side of women who were often marginalized. The problematic tendencies that occur in women in the sanctification process need to be mapped and linked to differences in brain structure and their way of thinking with men. The constant renewal of the mind also applies to women. Women's thoughts, feelings and wills are sometimes distorted due to physiological factors. The exegesis of Romans 12:2 makes it clear how women must continue to change in the renewal of mind to become more like Christ. Several women in the Bible are used as case studies to clarify the phenomenon under study.